Students Perception of Readability of Comic-Based Physics Ethnoscience Learning Media on Sound Wave Material Using Microsoft PowerPoint Application - Selly Diani Sari (CV. Media Inti Teknologi, 2022)
This study aims to conduct a readability test in order to describe students' perceptions of comic-based physics ethnoscience learning media on sound wave material using the Microsoft PowerPoint application. This type of research is development research. The research instrument used was a student perception questionnaire with 10 questions given to 30 respondents who were students in 3 schools, namely SMA Negeri 1, SMA Negeri 6 and SMA Negeri 9 Bengkulu City. In this study, data analysis used quantitative descriptions. Based on the results of the data obtained, it can be concluded that the comic-based physics ethnoscience learning media on sound wave material using the Microsoft PowerPoint application is very good based on the perceptions of students. This is based on the data obtained that of all statements regarding the readability of comic-based physics ethnoscience learning media, almost all of them were answered with the largest percentage being in the very good and good answer choices. This means that students agree with the statements offered on each question they fill in the perception sheet. Based on the data obtained, the average percentage of content quality aspect is 83%, the aspect of time allocation is 80% and the grammatical aspect is 87.5%. So it can be concluded from these three aspects that the module developed is very good with an overall average percentage of 83.5%.